Writing in our time : Canada's radical poetries in English (1957-2003) - Butling, Pauline (Wilfrid Laurier University Press, 2005)
Process poetics is about radical poetry - poetry that challenges dominant world views, values, and aesthetic practices with its use of unconventional punctuation, interrupted syntax, variable subject positions, repetition, fragmentation, and disjunction. To trace the aesthetically and politically radical poetries in English Canada since the 1960s, Pauline Butling and Susan Rudy begin with the "upstart" poets published in Vancouver's TISH: A Poetry Newsletter, and follow the trajectory of process poetics in its national and international manifestations through the 1980s and '90s. The poetics explored include the works of Nicole Brossard, Daphne Marlatt, B P Nichol, George Bowering, Jeff Derksen, Clare Harris, Erin Moure, and Lisa Roberston. They also look at books by older authors published after 1979, including Robin Blaser, Robert Kroetsch, and Fred Wah. A historiography of the radical poets, and a roster of the little magazines, small press publishers, literary festivals and other such sites that have sustained poetic experimentation, provide context.